Bài 1: Cho đa thức
A(x) = 3x4 – 3/4x3 + 2x2 – 3
B(x) = 8x4 + 1/5x3 – 9x + 2/5
Tính : A(x) + B(x); A(x) - B(x); B(x) - A(x);
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) A(x) = 2x3 + 5 + x2 - 3x - 5x3 - 4
= 2x3 - 5x3 + x2 - 3x + 5 - 4
= -3x3 + x2 - 3x + 1
B(x) = -3x4 - x3 + 2x2 + 2x + x4 - 4 - x2
= -3x4 + x4 - x3 + 2x2 - x2 + 2x - 4
= -2x4 - x3 + x2 + 2x - 4
b)
H(x) = A(x) - B(x)
H(x) = (-3x3 + x2 - 3x + 1) - (-2x4 - x3 + x2 + 2x - 4)
= -3x3 + x2 - 3x + 1 + 2x4 + x3 - x2 - 2x + 4
= 2x4 - 3x3 + x3 + x2 - x2 - 3x - 2x + 1 + 4
= 2x4 - 2x3 -5x + 5
a: \(=\dfrac{2x^4-2x^3-2x^2-3x^3+3x^2+3x+x^2-x-1}{x^2-x-1}\)
\(=2x^2-3x+1\)
a: \(A=-5x^3+9x^3-2x^2-2x^2+x-x+1\)
\(=4x^3-4x^2+1\)
\(B=-4x^3+2x^3-2x^2+2x^2+6x-9x-2\)
\(=-2x^3-3x-2\)
\(C=x^3-6x^2+2x-4\)
b: \(A\left(x\right)+B\left(x\right)-C\left(x\right)\)
\(=4x^3-4x^2+1-2x^3-3x-2+x^3-6x^2+2x-4\)
\(=3x^3-10x^2-x-4\)
a) \(P\left(x\right)=3x^3-x^2-2x^4+3+2x^3+x+3x^4-x^2-2x^4+3+2x^3+x+3x^4\)
\(=2x^4+7x^3-2x^2+2x+6\)
\(Q\left(x\right)=-x^4+x^2-4x^3-2+2x^2-x-x^3-x^4+x^2-4x^3-2+2x^2-x-x^3\)
\(=-2x^4-10x^3+6x^2-2x-4\)
b) \(P\left(x\right)+Q\left(x\right)=2x^4+7x^3-2x^2+2x+6-2x^4-10x^3+6x^2-2x-4\)
\(=-3x^3+4x^2+2\)
a: \(C\left(x\right)=A\left(x\right)+B\left(x\right)\)
\(=3x^4-4x^3+5x^2-4x-3-3x^4+4x^3-5x^2+2x+6\)
=-2x+3
b: Đặt C(x)=0
=>-2x+3=0
hay x=3/2
a: P(x)=6x^3-4x^2+4x-2
Q(x)=-5x^3-10x^2+6x+11
M(x)=x^3-14x^2+10x+9
b: \(C\left(x\right)=7x^4-4x^3-6x+9+3x^4-7x^3-5x^2-9x+12\)
=10x^4-11x^3-5x^2-15x+21
b: \(=\dfrac{2x^4-2x^3-2x^2-3x^3+3x^2+3x+x^2-x-1}{x^2-x-1}\)
\(=2x^2-3x+1\)
\(A(x)+B(x)=3x^4-\dfrac{3}{4}x^3+2x^2-3+8x^4+\dfrac{1}{5}x^3-9x+\dfrac{2}{5}\)
\(=11x^4-\dfrac{11}{20}x^3+2x^2-9x-\dfrac{13}{5}\)
__________________________________________________
\(A(x)-B(x)=3x^4-\dfrac{3}{4}x^3+2x^2-3-8x^4-\dfrac{1}{5}x^3+9x-\dfrac{2}{5}\)
\(=-5x^4-\dfrac{19}{20}x^3+2x^2+9x-\dfrac{17}{5}\)
__________________________________________________
\(B(x)-A(x)=8x^4+\dfrac{1}{5}x^3-9x+\dfrac{2}{5}-3x^4+\dfrac{3}{4}x^3-2x^2+3\)
\(=5x^4+\dfrac{19}{20}x^3-2x^2-9x+\dfrac{17}{5}\)
Bài 1
\(A\left(x\right)+B\left(x\right)=3x^4-\dfrac{3}{4}x^3+2x^2-3+8x^4+\dfrac{1}{5}x^3-9x+\dfrac{2}{5}=11x^4-\dfrac{11}{20}x^3+2x^2-9x-\dfrac{13}{5}\)
\(A\left(x\right)-B\left(x\right)=-5x^4-\dfrac{19}{20}x^3+2x^2+9x-\dfrac{17}{5}\)
\(B\left(x\right)-A\left(x\right)=5x^4+\dfrac{19}{20}x^3-9x-2x^2+\dfrac{17}{5}\)